High resolution photoemission yield study of the GaAs(100) surface cleaned by atomic hydrogen - Tomkiewicz, Paweł; Kościelniak, Piotr; Girycki, Adam; Szuber, Jacek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
High-resolution photoemission yield spectroscopy (PYS) has been used to study the electronic properties of space charge layer of the real GaAs(100) surface cleaned by atomic hydrogen. The ionization energy, work function and interface Fermi level position were determined as a function of hydrogen dose. Moreover, the evolution of effective density of filled electronic states localized in the band gap and in the upper part of the valence band was observed. Our experiments showed that for the hydrogen dose up to 104 L H2 the contamination etching stage occurs for which the interface Fermi level position EF – Ev reaches a value of 1.06 eV. For the higher hydrogen dose at the level 105 L H2 the interface Fermi level position EF – Ev reaches a value of 0.75 eV which corresponds to the degradation of GaAs(100) surface that becomes covered by metallic Ga.
Optica Applicata, Vol. 35, 2005, nr 3, s. 385-391
Keywords: optyka; GaAs; atomic hydrogen cleaning; photoemission yield spectroscopy (PYS); surface states; interface Fermi level pinning; work function; ionization energy